2002
DOI: 10.1046/j.1365-2141.2002.03940.x
|View full text |Cite
|
Sign up to set email alerts
|

Does isochromosome 7q mandate bone marrow transplant in children with Shwachman–Diamond syndrome?

Abstract: Summary. We report on nine children with Shwachman–Diamond syndrome (SDS), eight of whom had clonal abnormalities of chromosome 7. Seven children had an isochromosome 7 [i(7)(q10)] and one a derivative chromosome 7, all with an apparently identical (centromeric) breakpoint. Children with SDS are predisposed to myelodysplasia (MDS) and acute myeloid leukaemia (AML) often with chromosome 7 abnormalities. Allogeneic transplants have been used to treat these children, however, they are a high‐risk transplant group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 31 publications
2
30
0
2
Order By: Relevance
“…Two recurrent cytogenetic anomalies have been observed, i(7)(q10) and del(20q), which can be indolent and sometimes even transient. [25][26][27][28][29][30][31][32][33] However, these same abnormalities can also announce or be associated with a frank malignant outcome, [34][35][36] as we observed in two cases in this survey. In addition to the patients with i(7)(q10) and del(20q), we also observed an indolent profile in two other patients, one with t(16;20) in addition to i(7)(q10) and one with a complex abnormality of chromosome 9 (Online Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Two recurrent cytogenetic anomalies have been observed, i(7)(q10) and del(20q), which can be indolent and sometimes even transient. [25][26][27][28][29][30][31][32][33] However, these same abnormalities can also announce or be associated with a frank malignant outcome, [34][35][36] as we observed in two cases in this survey. In addition to the patients with i(7)(q10) and del(20q), we also observed an indolent profile in two other patients, one with t(16;20) in addition to i(7)(q10) and one with a complex abnormality of chromosome 9 (Online Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 53%
“…Despite the small numbers of patients analyzed, there was a significant difference in survival between patients receiving HSCT for non-malignant SC and those undergoing the procedure for leukemic transformation. Taking into account 33 published original cases 5,18,22,23,25,[43][44][45][46][47][48][49][50][51][52][53][54][55] of HSCT for SDS for which this information is mentioned, the survival after HSCT was significantly (P<0.001) different between the 22 patients with MDS/acute leukemia (17 deaths) and the 11 patients with Table 1. Univariate analysis of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature on HSCT in SDS patients is limited and consists mainly of case reports. [19][20][21][22][23][24][25][26][27][28][29] Vibhakar et al 30 recently reviewed the published experience with HSCT in SDS patients and reported a total of 28 patients, including their own. All but four patients received ablative conditioning regimens containing CY with or without TBI/ TLI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of nine SDS patients with isochromosome 7q found only one of three survivors in those undergoing HSCT, while six nontransplanted patients were alive without progressive aplasia or leukemia. 27 With regards to the optimal myeloablative preparative regimen in SDS, consideration should be given to avoid potentially cardio-toxic agents (ie cyclophosphamide) due to several reports of SDS patients developing cardiac insufficiency following HSCT. 13,28 However as summarized in Table 4 several patients have been successfully transplanted with cyclophosphamide containing regimens.…”
Section: Discussionmentioning
confidence: 99%